2012
DOI: 10.1292/jvms.11-0522
|View full text |Cite
|
Sign up to set email alerts
|

Production of GM-CSF Mediated by Cysteine Protease of Der f in Canine Keratinocytes

Abstract: ABSTRACT. House dust mite (HDM) allergens are the most common allergens for induction of IgE-mediated hypersensitivity. Recently, epicutaneous sensitization with HDM allergens has been emphasized in the development of atopic dermatitis (AD) by producing various soluble factors in keratinocytes. Among the soluble factors, GM-CSF is a key molecule that activates Langerhans cells, antigen-presenting cells in the epidermis. In the present study, we investigated the effects of Dermatophagoides farinae (Der f) on GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…93 The GM-CSF production was suppressed by addition of a cysteine protease inhibitor, suggesting that its production was most likely mediated via PAR-2 by Der f 1, which is one of the major allergens and a cysteine protease. 93 Similar to Der f 1, papain, a naturally derived cysteine protease, also induced GM-CSF production with translocation of nuclear factor of activated T cells (NFAT) in CPEK, and production was partially inhibited by ciclosporin. 94 These results suggest that GM-CSF production in CPEK activated via PAR-2 may be regulated not only by NFAT, but also by another transcription factor, such as nuclear factor-kB (NF-kB) or activator protein-1 (AP-1).…”
Section: Keratinocyte-derived Cytokines and Chemokinesmentioning
confidence: 96%
See 2 more Smart Citations
“…93 The GM-CSF production was suppressed by addition of a cysteine protease inhibitor, suggesting that its production was most likely mediated via PAR-2 by Der f 1, which is one of the major allergens and a cysteine protease. 93 Similar to Der f 1, papain, a naturally derived cysteine protease, also induced GM-CSF production with translocation of nuclear factor of activated T cells (NFAT) in CPEK, and production was partially inhibited by ciclosporin. 94 These results suggest that GM-CSF production in CPEK activated via PAR-2 may be regulated not only by NFAT, but also by another transcription factor, such as nuclear factor-kB (NF-kB) or activator protein-1 (AP-1).…”
Section: Keratinocyte-derived Cytokines and Chemokinesmentioning
confidence: 96%
“…It was also shown that keratinocytes from nonlesional skin of AD subjects exhibited increased spontaneous and PMA‐stimulated production of GM‐CSF . In dogs, CPEK were found to produce GM‐CSF upon stimulation by a house dust mite (HDM) allergen, Dermatophagoides farinae (Der f) . The GM‐CSF production was suppressed by addition of a cysteine protease inhibitor, suggesting that its production was most likely mediated via PAR‐2 by Der f 1, which is one of the major allergens and a cysteine protease .…”
Section: Keratinocyte‐derived Chemokines and Cytokines That Are Direcmentioning
confidence: 99%
See 1 more Smart Citation
“…In canine keratinocytes, Der f 1, a major allergen of Der f, was reported to upregulate mRNA transcription of GM‐CSF . We recently reported that GM‐CSF production in the CPEK cell line was significantly enhanced by stimulation with Der f, which was completely inhibited by a cysteine protease inhibitor . In canine keratinocytes, however, the signalling pathway for GM‐CSF production, mediated by cysteine proteases, has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…16 We recently reported that GM-CSF production in the CPEK cell line was significantly enhanced by stimulation with Der f, which was completely inhibited by a cysteine protease inhibitor. 17 In canine keratinocytes, however, the signalling pathway for GM-CSF production, mediated by cysteine proteases, has not been clarified. In order to develop a molecular targeting therapy, the signalling pathway of GM-CSF production should be clarified.…”
Section: Introductionmentioning
confidence: 99%